STRUCTURE OF LIMULUS STRIATED MUSCLE : The Contractile Apparatus at Various Sarcomere Lengths - Dewey, Maynard M. (The Rockefeller University Press, 1973)
The musculature of the telson of Limulus polyphemus L. consists of three dorsal muscles: the medial and lateral telson levators and the telson abductor, and one large ventral muscle; the telson depressor, which has three major divisions: the dorsal, medioventral, and lateroventral heads. The telson muscles are composed of one type of striated muscle fiber, which has irregularly shaped myofibrils. The sarcomeres are long, with discrete A and I and discontinuous Z bands. M lines are not present. H zones can be identified easily, only in thick (1.0 µm) longitudinal sections or thin cross sections. In lengthened fibers, the Z bands are irregular and the A bands appear very long due to misalignment of constituent thick filaments. As the sarcomeres shorten, the Z lines straighten somewhat and the thick filaments become more aligned within the A band, leading to apparent decrease in A band length. Further A band shortening, seen at sarcomere lengths below 7.4 µm may be a function of conformational changes of the thick filaments, possibly brought about by alterations in the ordering of their paramyosin cores.